Neurofibromatosis: A brief review for the dental health care professional - ADAMU, VE; Adebo, Dorcas Ojone; Eneojo, Ndidiamaka Ijeoma F. (Orapuh Journal, 2021)
Neurofibromatosis is a genetic neurological disorder that affects cell growth in nerve tissue. It produces tumors, which may become malignant, and may cause severe pain and debilitation, learning disabilities, behavioural dysfunction, and hearing and vision loss. Sporadic cases of this disorder have been reported in some parts of the oral and maxillofacial complex. It is important for dental health care professionals to be aware of the characteristics of this disorder so they may evolve strategies to promote oral health and improve the quality of life for sufferers. This review paper provides summarized information on the concept, classification, epidemiology, aetiology, oral manifestations, other signs and symptoms, diagnosis, and management of neurofibromatosis that may be necessary for the practice of the dental operator.